Accessing equity: challenges middle-income families face finding high quality childcare - Vines, Shere'lle Ramsey (Kansas State University, 2020)
Childcare is a necessity for many parents today. Some parents utilize childcare for learning opportunities, others use it as a form of respite, but for the majority of families, childcare is essential to them earning a living. Whatever the reason, children should have access to the highest quality of care. The gap between the very poor and very wealthy is growing and the middle-class families and children are the most vulnerable for lost wages, financial uncertainty, and lower quality childcare. This report proposes a hypothetical parent-centered volunteer-driven program to help alleviate the confusion, frustration, and stress related to childcare access and affordability, but in no means serves as a sufficient solution to the problem families everywhere are facing. It also addresses social justice and equity issues surrounding this dilemma and offers suggestions to offset the negative outcomes of expensive, low-quality childcare on children and families.
Keywords: High quality; Childcare; Middle income; Cost